2020
DOI: 10.3389/fgene.2020.00659
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Network Analysis Reveals Alternative Splicing-Related lncRNAs in Hepatocellular Carcinoma

Abstract: It is increasingly appreciated that long non-coding RNAs (lncRNAs) associated with alternative splicing (AS) could be involved in aggressive hepatocellular carcinoma. Although many recent studies show the alteration of RNA alternative splicing by deregulated lncRNAs in cancer, the extent to which and how lncRNAs impact alternative splicing at the genome scale remains largely elusive. We analyzed RNA-seq data obtained from 369 hepatocellular carcinomas (HCCs) and 160 normal liver tissues, quantified 198,619 iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…This lncRNA impairs the binding of a repressive chromatin-splicing adaptor complex important for mesenchymal-specific splicing, by recruiting PcG proteins and the histone demethylase KDM2a. More recently, Singer and colleagues (Singer et al 2019 ) characterised Paupar, a lncRNA that interacts with SR proteins to promote the alternative splicing of PAX6 in pancreatic glucagon-producing α cells and computational analysis of hepatocellular carcinoma RNA-Seq samples predicted hundreds of splicing-related lncRNAs (Wang et al 2020 ).…”
Section: Functions and Mechanisms Of Action Of Drosophila ...mentioning
confidence: 99%
“…This lncRNA impairs the binding of a repressive chromatin-splicing adaptor complex important for mesenchymal-specific splicing, by recruiting PcG proteins and the histone demethylase KDM2a. More recently, Singer and colleagues (Singer et al 2019 ) characterised Paupar, a lncRNA that interacts with SR proteins to promote the alternative splicing of PAX6 in pancreatic glucagon-producing α cells and computational analysis of hepatocellular carcinoma RNA-Seq samples predicted hundreds of splicing-related lncRNAs (Wang et al 2020 ).…”
Section: Functions and Mechanisms Of Action Of Drosophila ...mentioning
confidence: 99%
“…Since then, a number of large human studies have been published so we have updated our review to include these and other new studies that further support the concept that alternative splicing is an early feature of liver disease. While RNA splicing changes have been documented in HCC (8)(9)(10)(11)(12)(13)(14)(15)(16) and reviewed elsewhere (144)(145)(146), most studies in early liver disease, NAFLD or NASH, have focused on total mRNA changes rather than changes in individual mRNA isoforms and alternative splicing (48)(49)(50). These studies, however, can be informative as changes in the expression of splicing machinery components can be indicative of changes in RNA splicing.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recent studies have shown that changes in RNA splicing and RNA binding protein expression occur during the maturation of the liver (4,5), are associated with aging and sexual dimorphism in the liver (6), and have also been documented in hepatocellular carcinoma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), but little is known about changes in RNA splicing in early liver disease (17). Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in western countries, affecting almost 25% of the adult population in the world (18).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the RWMG model algorithm was used to analyse and predict the lncRNAs related to AS. This is the first time that a large-scale complex network has been integrated to predict the lncRNAs that regulate AS events in cancers, which is of great significance for discovering potential tumour markers [ 67 ].…”
Section: Introductionmentioning
confidence: 99%